Pendidikan Islam menuju Universitas Riset dalam Perspektif Al Qur’an - Burhanuddin, Cepi; Abdul Muid Nawawi (Institut Muslim Cendekia, 2026)
Current global higher education is undergoing a transformation toward the Research University model; however, in the context of Islamic education, this discourse often falls into a technocratic approach that neglects the Quranic epistemological foundations. This study aims to discuss how concepts within the Quran can serve as a basis for building and developing research universities in the global era. The method employed is qualitative library research with a philosophical-epistemological analysis approach. Data sources consist of relevant primary and secondary scientific works, analyzed using thematic and descriptive analysis techniques. The results show that the